2020
DOI: 10.5194/wcd-2020-48
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A process-based anatomy of Mediterranean cyclones: From baroclinic lows to tropical-like systems

Abstract: Abstract. In this study, we address the question of the atmospheric processes that turn Mediterranean cyclones into severe storms. Our approach applies on-line potential vorticity (PV) budget diagnostics and piecewise PV inversion to WRF model simulations of the mature stage of 100 intense Mediterranean cyclones. We quantify the relative contributions of different processes to cyclone development and therefore deliver, for the first time, a comprehensive insight into the variety of cyclonic systems that develo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 63 publications
3
7
0
Order By: Relevance
“…Temperature and geopotential height had the lowest anomalies in the northern quadrants. The finding supports that of Flaounas et al (2015aFlaounas et al ( , 2021aFlaounas et al ( , 2021b who showed that the temperature in Mediterranean cyclones is lower in the northern quadrants than Potential vorticity is helpful to understand formation and decay of these cyclones. It had positive values in all quadrants of the cyclone at 850 hPa (Figure 4a, in colour) and 500 hPa (Figure 4b, in colour), which suggested a high release of latent heat by condensation.…”
Section: Overall Associated Atmospheric Circulation At 850 and 500 Hpasupporting
confidence: 89%
See 2 more Smart Citations
“…Temperature and geopotential height had the lowest anomalies in the northern quadrants. The finding supports that of Flaounas et al (2015aFlaounas et al ( , 2021aFlaounas et al ( , 2021b who showed that the temperature in Mediterranean cyclones is lower in the northern quadrants than Potential vorticity is helpful to understand formation and decay of these cyclones. It had positive values in all quadrants of the cyclone at 850 hPa (Figure 4a, in colour) and 500 hPa (Figure 4b, in colour), which suggested a high release of latent heat by condensation.…”
Section: Overall Associated Atmospheric Circulation At 850 and 500 Hpasupporting
confidence: 89%
“…Flaounas et al (2015aFlaounas et al ( , 2021b for Mediterranean cyclones and with Davis et al (2013), Tamarin and Kaspi (2016) and Vanniere et al…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…This alignment is a so-called PV tower (Rossa et al, 2000;Čampa and Wernli, 2012), which has also been observed in intense Mediterranean cyclones (e.g., Miglietta et al, 2017). In a recent study, Flaounas et al (2021) found that both PV anomalies are contributing to the cyclonic circulation. However, their relative contribution might strongly vary from case to case.…”
Section: Introductionmentioning
confidence: 65%
“…In some case studies of Mediterranean cyclones near the Alps, turbulence, particularly in the boundary layer, was found to produce the lower-tropospheric PV (Flaounas et al, 2021). This PV originates from positive PV filaments, socalled PV banners (Aebischer and Schär, 1998;Rotunno et al, 1999;Epifanio and Durran, 2002;Schär et al, 2003;Flamant et al, 2004), horizontally extending from the mountains to the Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%